Penerapan Strategi Pembelajaran Berbasis Masalah dalam Upaya Meningkatan Keterampilan Menulis Teks Negosiasi bagi Siswa SMA Negeri 2 Labuapi - Rojiati Rojiati (UNDIKMA, 2020)
This study aims to improve the writing skills of negotiation texts through the application of problem-based learning strategies. This research is a classroom action research with the research subjects of class X MIPA 2 SMA Negeri 2 Labuapi consisting of 25 students. The research instrument used tests, observations, document analysis, interviews, and questionnaires. The data analysis technique used in this research was qualitative and quantitative descriptive analysis. The results of this study indicate that in the process there is an increase in student enthusiasm in participating in learning, student interaction in groups, and student attention. This can be shown from the results of observations during the learning process. The product improvement can be seen with the increase in the students' writing value of negotiating text. In the pre-cycle there were 16 students who had not yet completed it and in the first cycle there were still 6 students who had not finished, and in the second cycle it increased again, that all 25 students had all completed. These results indicate that the application of problem-based learning strategies can increase student activeness in teaching and learning activities and can improve writing negotiation text skills for class X MIPA 2 SMA Negeri 2 Labuapi.